Intimate Relationships and Heart Disease - Rokach, Ami (Journal of Psychology and Psychotherapy Research, 2019)
This article reviews the connection between intimate relationships, which provide support, safety and belonging, and illness in general, and particularly, coronary heart disease which is on the rise. Personal and environmental contributors to CHD are reviewed, and the strong connection between intimacy, or lack of, and health are highlighted.